2016
DOI: 10.1002/iid3.103
|View full text |Cite
|
Sign up to set email alerts
|

Parallel reductions of IgE and exhaled nitric oxide after optimized anti‐inflammatory asthma treatment

Abstract: Immunoglobulin E (IgE) is crucial for the development of airway inflammation in atopic asthma, and inhibition of IgE using monoclonal antibodies is now part of asthma therapy. However, the impact of ordinary anti‐inflammatory treatment on IgE is unclear. The aim of this study was to investigate if optimization of treatment with inhaled corticosteroid (ICS) and leukotriene‐receptor antagonist (LTRA) according to symptoms or exhaled nitric oxide (FENO) levels over a one‐year period affects IgE concentrations. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In the present study no associations between IgE or any of the inflammatory markers and sickness behaviour were found. However, in an earlier report from the same study sample, a reduction in perennial, total and all specific IgE was significantly associated with an improvement in asthma-related quality of life, 27 suggesting that certain IgE measures might be related to other factors than sickness behaviour relevant for subjective health perception. Hence, measuring levels of IgE could be a valuable clinical complement when evaluating variables associated with asthma-related quality of life, self-rated health and other patient-reported outcomes in asthma 27 and future research might delineate if IgE differs from other disease-specific variables in its relation to indices of subjective health.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…In the present study no associations between IgE or any of the inflammatory markers and sickness behaviour were found. However, in an earlier report from the same study sample, a reduction in perennial, total and all specific IgE was significantly associated with an improvement in asthma-related quality of life, 27 suggesting that certain IgE measures might be related to other factors than sickness behaviour relevant for subjective health perception. Hence, measuring levels of IgE could be a valuable clinical complement when evaluating variables associated with asthma-related quality of life, self-rated health and other patient-reported outcomes in asthma 27 and future research might delineate if IgE differs from other disease-specific variables in its relation to indices of subjective health.…”
Section: Discussionmentioning
confidence: 71%
“…In a previous study, a decrease in IgE concentrations was found to correlate with an improvement on both asthma control and asthma-related quality of life. 27 Furthermore, poor asthma-related quality of life has been shown to be associated with both poor self-rated health and increased sickness behaviour. 28 Thus, it could be of interest to investigate the relationship between asthma control and patient-reported outcome measurements in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yin SS et al also investigated the correlation between FENO and ICS efficacy in childhood bronchial asthma [ 65 ]. Syk et al highlights the possibility of IgE reduction with common asthma control drugs, which is confirmed in patients with persistent atopic asthma with annual optimization of ICS and LTRA treatment, resulting in a significant decrease in total IgE correlating with a reduction in FENO and an improvement in asthma control and quality of life [ 66 ]. Total IgE may predict asthma severity and the risk of exacerbations and loss of asthma control.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have utilized monoclonal antibody (mAb) treatment to attenuate signaling pathways involved in numerous airways diseases, including asthma and COPD (Arora, McDonald, Toews, & Huffnagle, 2006;Kondo et al, 2006;Kumar, Herbert, Webb, Li, & Foster, 2004;Syk et al, 2016). Monoclonal antibodies are thought to exhibit a number of advantages over small molecule based therapies; 1) mAbs are considered to exert greater specificity for the target molecule, 2) they do not form toxic metabolites following breakdown, and 3) they generally have longer half-lives (Chames, Van Regenmortel, Weiss, & Baty, 2009).…”
Section: Monoclonal Antibody Therapymentioning
confidence: 99%